Economic analysis of the digital economy - Goldfarb, Avi; Greenstein, Shane M.; Tucker, Catherine (Catherine Elizabeth) (National Bureau of Economic Research conference report., 2015)
As the cost of storing, sharing, and analyzing data has decreased, economic activity has become increasingly digital. But while the effects of digital technology and improved digital communication have been explored in a variety of contexts, the impact on economic activity - from consumer and entrepreneurial behaviour to the ways in which governments determine policy - is less well understood. This book explores the economic impact of digitisation, with each chapter identifying a promising new area of research.